Cuando Papá Noel cayó del cielo - Funke, Cornelia, 1958- (Tres edades. Biblioteca Funke, 2015)
When he and his caravan come crashing down to earth during a thunderstorm two weeks before Christmas, Santa is befriended by two children, Charlotte and Ben, who try to help him save the holiday from the tricks and moneymaking schemes of Gerold Geronimus Goblynch and to take off in time for his annual rounds.